Propiedades psicométricas del Drive for Muscularity Scale (DMS) en una muestra de hombres y mujeres jóvenes chilenos - Escandón Nagel, Neli; Baeza Rivera, María José; Larenas Said, Josefa; Caamaño Mardones, Esteban (Revista de Psicopatología y Psicología Clínica, 2021)
Drive for muscularity, although it mainly occurs in men, is also experienced by women. It is important to have instruments to measure this construct, which is the reason why the aim of this study was to evaluate the psychometric properties of the Drive for Muscularity Scale (DMS) in Chilean adolescents and young adults (n = 602). The DMS and the SATAQ-4 were administered. The confirmatory factor analysis showed two factors, one representing attitudes and the other behaviors, in addition to a second-order factor. This structure had a good fit for both sexes, although for women it was necessary to remove two items. Regarding sex, men showed higher scores and, with respect to age, adolescents manifested greater drive for muscularity. For both sexes a positive correlation between the DMS and the athletic/body ideal internalization scale was observed. These results confirm that the Chilean version of the DMS has adequate psychometric properties.